PENGARUH BUDAYA PERUSAHAAN, KEPEMIMPINAN, DAN PENGAMBILAN KEPUTUSAN TERHADAP KINERJA PIMPINAN DALAM MENGELOLA LINGKUNGAN - Diana Vivanti Sigit (Program Studi Manajemen Lingkungan, 2013)
The objectives of this research is aim at finding out information about the effect of corporate culture, leadership, and decision making on corporate supervisor the performance in managing environment. Eighty five supervisors of PT. Pembangunan Jaya Ancol, Tbk. were involved in this study. The data of the survey was analyzed by path analysis. The result shows as follows: (1) corporate culture has a direct effect on the supervisor’s performance (2) leadership has a dirrect effect on supervisor’s performance, (3) decision making has a dirrect effect on supervisor’s performance, (4) corporate culture has a dirrect effect on decision making, and (5) leadership has a dirrect effect on decision making. Based on these findings, it can be concluded that any change or variation occurred on supervisor’s performance might have been affected by corporate culture, leadership, and decision making.